저항성 유전자 도입과 벼 후대계통의 열악형질간의 관계분석 - 이창민(Chang-Min Lee); 박현수(Hyun-Su Park); 백만기(Man-Kee Baek); 서정필(Jung-Pil Suh); 정오영(O-Young Jeong); 윤성중(Song-Joong Yun); 김석만(and Suk-Man Kim) (Korean journal of breeding, 2021)
Interspecific and intersubspecific crosses have been an important strategy for rice breeding programs to obtain useful charactersby expanding genetic diversity. However, the wide cross routinely causes undesirable characters in rice, such as spikelet sterility and poorquality. In this study, we developed near-isogenic lines of R-gene (Xa4+xa5+Xa21+Pi40+Bph18) introgression population to investigate thegenetic relationship between the occurrence of poor characters and R-genes induced by MAS. The ANOVA analysis revealed that Pi40, Bph18,and Xa4 were associated with spikelet fertility (SF), ratio of ripened grain (RRG), third internode length (TIL), panicle extraction (PE), andprotein content (Pro), whereas others showed no association with the 14 traits tested. In the three-way ANOVA, the impact of two R-genes(Pi40 and Bph18) on the poor characters was independent, with no interaction with others. Quantitative trait locus (QTL) analysis identifiedQTLs for PE and TIL traits near Pi40, and in particular, QTLs for five traits (SF, RRG, TIL, PE, and Pro) were negatively affected aroundBph18. The occurrence of a poor character in R-gene pyramiding lines could be associated with linkage drag caused by the Bph18 gene. We speculate that the development of DNA markers that effectively eliminate poor characters will not only improve breeding efficiency usingMAS, but will also help improve traits of japonica rice through wide crossing. KCI Citation Count: 0